The architecture of misleading: How journalists spread inaccurate information on digital platforms - Pinto-Garzón, Karen; Meini, Cristina (Anàlisi, 2025)
Drawing on a semi-systematic review and a qualitative analysis of posts on Facebook and Instagram between November 2023 and March 2025, the article identifies several subtle practices through which news outlets mislead audiences, even when they can reasonably anticipate that these strategies will confuse typical users: (1) digitally manipulated images that fabricate or exaggerate threats; (2) authentic but decontextualised photographs that invite false associations; (3) emotional clickbait pairings of headlines and visuals in which corrective information is relegated to lengthy captions; and (4) ambiguous or omissive headlines that rely on pragmatic implicatures rather than explicit falsehoods. The analysis shows that journalistic disinformation on social media is often produced through editorial choices aligned with platform logics of visibility and engagement. Understanding these practices is key to rethinking media accountability in digital environments where most users engage only with headlines, thumbnails and brief snippets, rather than with full articles.